The Effect Of Marketing Mix On Students Loyalty Towards Instant Noodles With The Brands of INDOMIE, SEDAP, and ABC With Moderated Variety Seeking - Diani Arthantri (Institute of Computer Science (IOCS), 2021)
This research aims to know the effect of marketing mix on students loyalty of instant noodle with the brands of Indomie, Sedaap, and ABC which is moderated by variety seeking characteristics of consumers. This research was conducted in August-September 2010 at the Management Students Economic Faculty Sanata Dharma University Yogyakarta. Data were collected using questionnaire. The population of the research was Management Students of Economics Faculty, Sanata Dharma University Yogyakarta, from 2005-2008 batch who have consumed instant noodle of the brands of Indomie, Sedaap, and ABC. The sampling technique in this research is nonprobability accidental sampling. The samples were 100 respondents. The data analysis technique used were Multiple Linear Regression analysis and Regression Analysis with moderating effect. Results show that: 1) Marketing mix influences students loyalty. 2) Variety seeking characteristics moderates the influence of product on loyalty.